On the existence of an almost generalized weakly-symmetric Sasakian manifold admitting quarter symmetric metric connection - NURCAN, AYŞE FÜSUN (TAYLOR & FRANCIS LTD, 2019)
The object of the present work is to study an almost generalized weakly symmetric Sasakian manifold admitting quarter symmetric metric connection with a non-trivial example.
Keywords: Almost generalized weakly symmetric Sasakian manifolds; quarter symmetric metric connection